Some contributions of a psychological approach to the study of the sacred. Issue 4 (2nd October 2017) - Pargament, Kenneth I.; Oman, Doug; Pomerleau, Julie; Mahoney, Annette
ABSTRACT: This paper examines some of the contributions psychology is making to the study of the sacred and its role in human functioning. The focus here is not on the ontological reality of the sacred, but rather perceptions of the sacred. We suggest that psychological theory and research on this topic offers: a clarification of the meaning of the sacred; new knowledge about sanctification – the process through which people come to perceive the sacred in daily life; a response to criticisms about the scientific study of the sacred; a sharper perspective on the meanings of religion and spirituality; a method for measuring sanctification; knowledge about the ways perceptions of the sacred predict important aspects of human behavior, and; an understanding of the sacred as a product of psychological, social, institutional, cultural, and situational forces. We conclude that the sacred represents a vital phenomenon of interest for religious and spiritual study.